Simultaneous toughening of PPO/HIPS/Glass fiber reinforced composites with thermoplastic rubbers. Issue 11 (24th December 2013) - Tang, Weihua; Guo, Xuejiao; Li, Dapeng; Zhu, Enwei; Yuan, Huilin
ABSTRACT Simultaneously reinforced and toughened PPO/HIPS/SEBS/glass fiber (GF) 60/40/5/30 composites were successfully prepared with GF as reinforcing agent and SEBS as toughener. The formulation of PPO/HIPS/SEBS/GF quaternary composites was stepwise optimized by evaluating the effect of GF and SEBS on the processing, mechanical and thermal properties of the composites. The synergistic effects of GF reinforcement and elastomer toughening are attributed to high performance PPO/HIPS/SEBS/GF composites. Among the four elastomers studied, SEBS exhibited as effective toughener for PPO/HIPS matrix and the resulted PPO/HIPS/SEBS/GF composites presented a good combination of mechanical and thermal properties. The optimized PPO/HIPS/SEBS/GF 60/40/5/30 quaternary composites displayed a tensile strength of 123.6 MPa, a bending strength of 149.7 MPa, an unnotched impact strength of 46.6 KJ/m2 and a heat distortion temperature of 148.9°C. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40299.